Highly stabilized flexible transparent capacitive photodetector based on silver nanowire/graphene hybrid electrodes - Yooji Hwang (Nature Portfolio, 2021)
Abstract The need for photodetectors in various fields has gradually emerged, and several studies in this area are therefore being conducted. For photodetectors to be used in various environments, their transparency, flexibility, and durability must be ensured. However, the development of flexible photodetectors based on the current measurement techniques of conventional photodetectors has been difficult owing to the limitations of semiconductor materials. In this study, a new type of flexible and transparent capacitive photodetector was fabricated to address the shortcomings of conventional photodetectors. In addition, by introducing graphene electrodes to a new type of manufactured photodetector, devices with excellent overall chemical, thermal, and mechanical durability have been developed. Compared to photodetectors based on pristine Ag nanowire (AgNW) electrodes, AgNW/graphene hybrid electrode-based photodetectors exhibit a 20% higher photosensitivity. Also, the hybrid AgNW/graphene electrode on the dielectric layer exhibited low sheet resistance (~ 8 Ω/sq) and relatively high transmittance (~ 45%).